Tetrahedral amorphous carbon resistive memories with graphene-based electrodes. (14th September 2018) - Ott, A K; Dou, C; Sassi, U; Goykhman, I; Yoon, D; Wu, J; Lombardo, A; Ferrari, A C
Abstract: Resistive-switching memories are alternative to Si-based ones, which face scaling and high power consumption issues. Tetrahedral amorphous carbon (ta-C) shows reversible, non-volatile resistive switching. Here we report polarity independent ta-C resistive memory devices with graphene-based electrodes. Our devices show ON/OFF resistance ratios ̃, ten times higher than with metal electrodes, with no increase in switching power, and low power density ̃14 μ W μ m −2 . We attribute this to a suppressed tunneling current due to the low density of states of graphene near the Dirac point, consistent with the current–voltage characteristics derived from a quantum point contact model. Our devices also have multiple resistive states. This allows storing more than one bit per cell. This can be exploited in a range of signal processing/computing-type operations, such as implementing logic, providing synaptic and neuron-like mimics, and performing analogue signal processing in non-von-Neumann architectures.